Musykilat al-Tarbiyyah Tuwajihuha al-Thalabah fi Ta’allum al-Lughah al-Arabiyah li Ghairi al-Nathiqin biha - Istiqomah, Himatul -; Mahliatussikah, Hanik - (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
The rapid development of technology is expected to develop the teaching and learning of Arabic. However, due to some problems, this aim is yet to achieve. This descriptive qualitative research is to identify problems faced by Indonesian learners of Arabic and to explore the types of problems and the solutions. Based on a library research, there are two main problems in teaching and learning of Arabic. They are internal and external problems as well as linguistic and non-linguistic problems. Internal problems are related to learners while external problems are related to environment and teachers. Linguistic problems deal with sound system, vocabulary, semantics, syntax, morphology, and writing. Nonlinguistic problems are those dealing with school facility, family, and learners’ internal factors. Learners facing linguistic problems should be given exercises to improve their linguistic competence and those facing non-linguistic problems should be given motivation, feedback, and helped to view the process of Arabic learning as something fun. Families should consider the most appropriate school for their children. Schools, on the other hand, are responsible to give the best facilities such as experienced teachers and learning facilities that are able to boost learners’ language learning, as well as giving weak learners additional materials to improve their ability. This discussion is expected to reveal the factors causing the problems and identify their possible solutions. Thus, this research is significant as it contributes to solve problems in non-Arab learning of Arabic.